Viaggiare per ritrovare e poi rinunciare all’identità – l’esperienza di Giorgio Pressburger - Lukácsi, Margit (Verbum – Analecta Neolatina, 2019)
The article discusses the narrative experience of Giorgio Pressburger, the Hungarian- Italian-Jewish writer and dramatist. He argues in his writings that the concept of identity as a warranty of a people’s survival can reach the moment of getting rid of the obsession of identity, of coming to feel to be a member of “the human community of the living and the dead”.